DETERMINATION OF PURCHASE INTENT DETERMINATION OF PURCHASE INTENTION THROUGH BRAND AWARENESS AND PERCEIVED QUALITY (Case Study: For consumers PT. Sentosa Santosa Finance Tangerang area) - Sivaram, M.; Munawar, Niknik Ahmad; Ali, Hapzi (Dinasti International Journal of Management Science, 2019)
This study aims to analyze: 1) the effect of brand awareness on the purchase Intention of the customer CS Finance Tangerang area 2) the influence of brand awareness on perceived quality in customers CS Finance Tangerang area and 3) the influence of perceived quality on purchase decisition on CS Finance Tangerang area customers. This study uses a conclusive research design that is research designed to help decision making in determining, evaluating and choosing the best alternatives in solving research problems. The type of research that the author uses in the design of conclusive research is a type of descriptive research that is research that aims to explain the causal relationship between variables with the specification of a single cross-sectional design research technique in which data collection activities are carried out from one respondent for a particular moment. This research was analyzed with Structural Equation Modeling (SEM) analysis with Lisrel, a statistical modeling technique that is very cross-sectional, linear and general. Included in the Lisrel SEM is factor analysis, path analysis and regression. The study was conducted from February to August 2018. Respondents were 200 samples at CS Finance Tangerang area customers. The results of the study are: 1) the positive and significant influence of brand awareness on purchase intention on CS Finance Tangerang area customers 2) the positive and significant influence of brand awareness on perceived quality in consumers of CS Finance Tangerang area and 3) the influence positive and significant perceived quality of purchase intention in CS Finance Tangerang area consumers.